PENYUSUNAN RENCANA INDUK PENANGANAN KAWASAN RAWAN BENCANA DI KABUPATEN SINTANG, KALIMANTAN BARAT - Najib Najib; Wahju Krisna Hidayat (TEKNIK, 2009)
Sintang Residence is a region which has susceptible region of natural disaster mainly landslide and flood.As the result of that vulnerability, it is needed to do the research to determine zonation of susceptibility ofdisaster. Zonation of landslide is based on four parameters such as slope, annual rainfall, geology factorsand land use. Zonation of flood is based on monthly/daily rainfall, land use, topographic condition andflood terrains. Based on secondary data and primary data, Sintang residence can be divided into threesusceptibility landslide zones, i.e. intermediate, low and very low susceptible landslide zones. Susceptibleflood zones are divided into three zones i.e. high, intermediate and low susceptible flood zone. Landslidesin that area are happened due to some factors; among other things are the rocks weathered, high slopedirection and no retaining wall. Flood is happened mostly due to the position of residences which straightforward or less height toward river water level and that location near with the rivers. Flood occupied theresidences mostly pass terrain edge river or pass by Sub River or rubbish ditch that ended in the mainriver. The purposes of mitigation those disasters based on the land use